Winter Prevalence of Dengue Fever Followed by Immunosuppression Associated White Blood Cell Elevation: A Cross Sectional Study - Md Navim Kabir , Chowdhury (Bangladesh Journal of Medicine, 2024)
Background : As a tropical country, Bangladesh is very much vulnerable to Dengue fever. Though commodities are well familiar to this,it’s winter prevalence in recent times makes health authorities in a fix to introduce effective curative and preventive measures to prevent premature death. A single Aedes aegypti bite causes severe life threatening situations including death but the survivers also face immunosuppressions followed by repeated infections. Methods : 75 patients came to outdoor patient department and indoor for pyrexia, respiratory tract infection whose age group (32-47)+_ 2 years.41 patients were male and rest of 34 patients were female.15 male patients and 10 female patients who had history different co-morbidities and they were (42-45)+_ 2 years age group. Results : Among 41 male patients, 31 patients(76%) and 18 female patients (55%) who came to outdoor patient department with history of chronic dry cough, low grade fever with malaise. They suffered from dengue fever in recent winter. 19 male patients (61%) had history of hospitalization. This time we got leucocytosis ( White Blood Cell count > 15,000 /cumm^3 of blood) in 49 patients(65%).As 5 patients having other co-morbidities it turned into 53%.Prescribing broad spectrum antibiotic 10 patients got symptomatic relief and their WBC count found 11,000-13,000/cumm^3 of blood. Remaining 51% had moderate leucocytosis associated mild to moderate symptoms. Conclusion: Patients chronic systemic diseases indicate suspected DEN 2 & 3 prevalence which should be come under brief research for curative treatment. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 161